2015
DOI: 10.2298/tsci140524174z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intake air temperature on homogenous charge compression ignition combustion and emissions with gasoline and n-heptane

Abstract: In a port fuel injection engine, Optimized kinetic process (OKP) technology is implemented to realize HCCI combustion with dual-fuel injection. The effects of intake air temperature on HCCI combustion and emissions are investigated. The results show that dual-fuel control prolongs HCCI combustion duration and improves combustion stability. Dual-fuel HCCI combustion needs lower intake air temperature than gasoline HCCI combustion, which reduces the requirements on heat management system. As in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This causes the combustion process to expand toward the power stroke which causes incomplete combustion, and consequently emitting high amounts of HC and CO [15]. Moreover, the existence of high amounts of low reactivity fuel across the cylinder and especially at cold regions (gasoline near the wall and the crevices, where it is difficult for the fuel to burn) has a stronger effect than the oxidation processes enhancement [25].…”
Section: Resultsmentioning
confidence: 99%
“…This causes the combustion process to expand toward the power stroke which causes incomplete combustion, and consequently emitting high amounts of HC and CO [15]. Moreover, the existence of high amounts of low reactivity fuel across the cylinder and especially at cold regions (gasoline near the wall and the crevices, where it is difficult for the fuel to burn) has a stronger effect than the oxidation processes enhancement [25].…”
Section: Resultsmentioning
confidence: 99%
“…The values of constants present in the previous equation for methane, referred to in the literature, depending on the calculation algorithm adopted amount to: -variant I: 9 , E a = 48.4 kcal/mol, a = -0.3, b = 1.3 [30] -variant II: 6 , E a = 30.0 kcal/mol, a = -0.3, b = 1.3 [30] THERMAL SCIENCE, Year 2017, Vol. 21, No.…”
Section: The 0-dimensional Dual-fuel Engine Modelmentioning
confidence: 99%
“…In a number of research works on dual-fuel engines it was demonstrated that the operating parameters of a dual-fuel compression ignition engine depend significantly on the pilot dose size [1][2][3], pilot dose injection timing [1,4], amount and quality of gas supplied to the engine [5][6][7], and on the quantity and temperature of air aspired by the engine [8,9]. To ensure optimum use of the engine capabilities all those parameters have to be adjusted relative to the rotational speed and load.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the thermal efficiency of gasoline engines, new combustion modes, such as lean burn, 1 homogeneous charge compression ignition (HCCI) combustion 2,3 and spark-assisted compression ignition combustion (SACI), 4,5 have emerged in traditional spark ignition (SI) engines. HCCI combustion has received more attention from researchers because of its high thermal efficiency and low emissions.…”
Section: Introductionmentioning
confidence: 99%